Strategi Pembelian Terselubung Untuk Pemberantasan Peredaran Gelap Narkotika (Studi Pada Badan Narkotika Nasional Provinsi Lampung) - Fasyah, Karfika Rosaida; Dewi, Erna; Riski, Sri (Jurnal Multidisiplin, 2025)
The rapid development of technology and information has an impact on various aspects of people's lives. Along with the advancement of information technology, the crime rate has also increased rapidly. One of the most rampant crimes is the illicit trafficking of narcotics, which if misused can cause addiction and have a negative impact on vital organs. This study aims to analyze the extent to which the Lampung Province National Narcotics Agency (BNN) has formulated a strategy to combat the illicit trafficking of narcotics in its region by using the undercover buy method. This study uses a qualitative approach with a normative-empirical research approach. The results of the study show that the BNN investigation team uses an undercover purchase strategy to arrest drug dealers. The main target of this operation is large-scale drug dealers with evidence in the form of large amounts of narcotics.